Repositioning Teachers' Instructional Language Based on the Huma Betang Philosophy to Optimize Primary School Learning - Ichyatul Afrom; Widya Permata Dilla (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Teachers' instructional language serves as the primary medium for transferring knowledge, shaping character, and managing classrooms in primary schools. This study aims to analyze the urgency of primary school teachers' instructional language skills in balancing material complexity (intrinsic load) and minimizing informational distractions (extraneous load), while simultaneously integrating a humanist approach rooted in local wisdom. Employing a descriptive qualitative approach with a content analysis method, the study reveals that specific, empathetic, and adaptive linguistic structures tailored to the cognitive development of children aged 7–12 significantly enhance information retention and students' emotional engagement. Furthermore, the internalization of the Huma Betang philosophy and Belom Bahadat values within teachers' discourse is proven to cultivate a psychological safety zone that optimizes children's brain function.